Alignment of Lyapunov Vectors: A Quantitative Criterion to Predict Catastrophes? - Beims, Marcus W.; Gallas, Jason (Scientific Reports, 2016)
We argue that the alignment of Lyapunov vectors provides a quantitative criterion to predict catastrophes, i.e. the imminence of large-amplitude events in chaotic time-series of observables generated by sets of ordinary differential equations. Explicit predictions are reported for a Rössler oscillator and for a semiconductor laser with optoelectronic feedback.
EAM Import::2019-03-13